ANALISIS KINERJA PETUGAS TERMINAL SERVICE OFFICER DALAM MELAKUKAN PENGAWASAN TERHADAP FASILITAS TERMINAL DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Irzi Fakhrurrozi Khana; Suprapti (ADISAM PUBLISHER, 2024)
The Terminal Service Officer (TSO) assists airport service customers in the terminal area. The Airport Operation Landside and Terminal Service Improvement Unit is a division that provides services to airport users. In accordance with Article 1 paragraph 8 of the Standard Operating Procedure of PM 178 of 2015, the responsibilities of the Terminal Service Officer include setting objectives for service performance and being a reference for evaluation, responsible for supervising, monitoring, controlling, and coordinating with related units to maintain the terminal area and the land side of the airport, in accordance with the Standard Operating Procedures. Primary and secondary data were used in this study. The topic of this research is Terminal Service Officer. Three approaches were used to obtain data: documentation, interviews, and observations. Three informants were interviewed for this qualitative research approach: supervisors, information service officers, and terminal service officers. The results of this study show that low effectiveness and performance are caused by the breadth of responsibility of the position and limited human resources. Meanwhile, the workers who act as Terminal Service Officers have overcome obstacles in accordance with the relevant Standard Operating Procedures.